SISTEM INFORMASI DESA HUTARAJA KECAMATAN SIPOHOLON BERBASIS WEB - Sibagariang, Roida Ferawati; Siringoringo, Rimbun; Purba, Eviyanti Novita (Universitas Methodist Indonesia, 2023)
In this era of development, people are required to know and understand developments about the importance of existing technology. Technology makes it easy to help every human activity in the world of academia, builders and others, especially in the field of government. At present Hutaraja Village still uses a manual system which in the end the community cannot obtain the information needed at any time, so much information is not yet known. And activities to carry out data management processes, such as population data collection, and social assistance (social assistance) are still manualized using Microsoft Word and Microsoft Excel. So it is hoped that Hutaraja Village will use a web-based information system with the aim of making it easier for the community to get the information they need at any time connected to the internet and to make it easier for village officials to manage population data. By using several research methods, namely system design and analysis. With the implementation of an information system in Hutaraja Village, the delivery of information from the village to the community will be more effective.